“The Toughest Job”: Adkins v. Rumsfeld, Gender, Incentives, and the Uniformed Services Former Spouses’ Protection Act - Decker, Brian R. (Columbia Journal of Gender and Law, 2008)
Not much is written about Jessica Miller. She was a student of psychology, was born in 1982 or early 1983, and spent at least part of her childhood in Pike County, Kentucky. The last part is assumed because she is said to have married her “childhood sweetheart” and Pike County is the childhood home of her ex-husband, James Blake Miller (Blake). Blake has been the subject of much more publicity: a 2004 Los Angeles Times photograph captured a close-up of him: a Marine weary in the midst of the battle for Fallujah, Iraq. In the picture, a battered combat helmet frames a face caked with dirt and blood, Blake’s eyes are locked in the classic soldier’s thousand-yard stare, and a cigarette dangles from his lower lip. When the photo made the pages of a hundred U.S. newspapers and the cover of Time Magazine, Blake became an icon nicknamed “the Marlboro Man.” After he returned from his tour, Jessica helped diagnose him with post-traumatic stress disorder-which is the only reason the public knows she studied psychology.